The Validity Of Marriages Agreement Made After Ongoing Based Marriage Law In Indonesia - Intan Fajriyanti; Joko Hermawan Sulistyo; Munsharif Abdul Chalim (Jurnal Akta, 2018)
Mating agreement has been stipulated in Article 29 of Act No. 1 Of 1974. Married to the present agreement remains in the society. The problems examined in this study is: what are the factors occurrence marriage agreement, how the validity of the agreement to marry, and the legal consequences mating agreement executed after the course of the marriage. The method used is a normative legal research. The result of the first conclusion that the arrangement agreement are married in Indonesia in the Act include the Civil Code, the Marriage Act No. 1 of 1974, KHI and the Constitutional Court Decision No. 69 / PUU-XIII / 2016, and at the conclusion of research results mating agreement made after the course of a legal marriage do not violate the boundaries of the law, religion, and morality.Keywords: Agreement; Mating Agreement; Marriage Law.